2021
DOI: 10.1111/iju.14567
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcomes of external beam radiation therapy for oligometastatic prostate cancer: A combination of prostate‐targeted treatment and metastasis‐directed therapy

Abstract: Abbreviations & Acronyms 3D-CRT = three-dimensional conformal radiotherapy A-ADT = adjuvant androgen deprivation therapy ADT = androgen deprivation therapy ARAT = androgen receptor axistargeted BF = biochemical failure CAB = combined androgen blockade CF = clinical failure CI = confidence interval CRPC = castration-resistant prostate cancer CT = computed tomography EBRT = external beam radiation therapy IMRT = intensity-modulated radiation therapy iPSA = pretreatment prostatespecific antigen LH-RH = luteinizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…3 For synchronous OMPCa, a large prospective trial (STAM-PEDE) showed improved survival with prostate-targeted treatment in patients with low metastatic burdens. 1 Aizawa et al 4 report that the addition of metastasis-targeted treatment to prostate-targeted treatment in patients with synchronous OMPCa resulted in good, long-term, disease-free survival with acceptable complications, a finding that has not been adequately investigated. It is hoped that the results of prospective studies will confirm the usefulness of this treatment.…”
mentioning
confidence: 99%
“…3 For synchronous OMPCa, a large prospective trial (STAM-PEDE) showed improved survival with prostate-targeted treatment in patients with low metastatic burdens. 1 Aizawa et al 4 report that the addition of metastasis-targeted treatment to prostate-targeted treatment in patients with synchronous OMPCa resulted in good, long-term, disease-free survival with acceptable complications, a finding that has not been adequately investigated. It is hoped that the results of prospective studies will confirm the usefulness of this treatment.…”
mentioning
confidence: 99%